Progress, problems, and possibilities of GIS in the South Caucasus: an international workshop summary. (24th April 2018) - Lindsay, Ian; Rubinson, Karen S.; Greene, Alan F.; Hammer, Emily; Lawrence, Dan
Abstract : In response to increased international collaboration in archaeological research of the South Caucases, a recent workshop has addressed important issues in applying GIS to the study of heavily modified landscapes in the former Soviet republics of Armenia, Azerbaijan and Georgia.